(untitled) (Archives of Physiotherapy, 2018)
Background: Abdominal muscles have stiffer appearance in individuals with spastic type cerebral palsy (STCP) than in their typically developing (TD) peers. This apparent stiffness has been implicated in pelvic instability, mal-rotation, poor gait and locomotion. This study was aimed at investigating whether abdominal muscles activation patterns from rest to activity differ in the two groups. Method: From ultrasound images, abdominal muscles thickness during the resting and active stages was measured in 63 STCP and 82 TD children. The thickness at each stage and the change in thickness from rest to activity were compared between the two groups. Results: Rectus abdominis (RA) muscle was the thickest muscle at rest as well as in active stage in both groups. At rest, all muscles were significantly thicker in the STCP children (p < 0.001). From rest to active stages muscle thickness significantly increased (p < 0.001) in the TD group and significantly decreased (p < 0.001) in the STCP children, except for RA, which became thicker during activity in both groups. In active stages, no significant differences in the thickness in the four abdominal muscles were found between the STCP and the TD children. Conclusion: Apart from the RA muscle, the activation pattern of abdominal muscles in individuals with STCP differs from that of TD individuals. Further studies required for understanding the activation patterns of abdominal muscles prior to any physical fitness programmes aimed at improving the quality of life in individuals with STCP.